2017
DOI: 10.1186/s12950-017-0171-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection of circulating natural antibodies to inflammatory cytokines in type-2 diabetes and clinical significance

Abstract: BackgroundInflammatory cytokines have been demonstrated to be involved in developing insulin resistance and type-2 diabetes (T2D). Natural antibodies in the circulation have protective effects on common diseases in humans. The present study was thus designed to test the hypothesis that natural antibodies against inflammatory cytokines could be associated with T2D.MethodsAn enzyme-linked immunosorbent assay (ELISA) was developed in-house to detect plasma IgG against peptide antigens derived from interleukin 1α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…However, a wide variety of nucleated cells, including EPCs, are potential sources of IL8 (46). Previous studies have indicated that in patients with type 2 DM, IL8 is elevated in the plasma compared with that in healthy subjects (47). IL8 is considered a canonical angiogenic factor and has a crucial role in the protection of EPCs for attenuating injury and prompting recovery of damaged tissues (4850).…”
Section: Discussionmentioning
confidence: 99%
“…However, a wide variety of nucleated cells, including EPCs, are potential sources of IL8 (46). Previous studies have indicated that in patients with type 2 DM, IL8 is elevated in the plasma compared with that in healthy subjects (47). IL8 is considered a canonical angiogenic factor and has a crucial role in the protection of EPCs for attenuating injury and prompting recovery of damaged tissues (4850).…”
Section: Discussionmentioning
confidence: 99%
“…Under hyperglycemic states, crosstalk between PGs and other inflammatory factors has a profound effect on glycemic control. Systemic inflammatory responses are upregulated in T2dM individuals (122), characterized by elevated levels of lipid molecules, including PGs and cytokines such as TNF-α (123), IL-1β (124), IL-6 (125) and IL-8 (126), in correspondence with the decline of their natural antibodies (127). In PG signaling, cOX-2 is involved in IL-1β-induced auto-stimulation in islets (111).…”
Section: Pgs and Hyperglycemiamentioning
confidence: 99%
“…The MR is involved in the activation of numerous signaling pathways in vascular smooth muscle cells (VSM-Cs) including extracellular signal-regulated kinase (ERK), mitogen-activated protein kinase (MAPK), the tyrosine kinase c-Src, c-jun N terminal kinase (JNK), epidermal growth factor receptor (EGFR) or myosin phosphate target subunit-1 (MYPY1), leading to VSMC stress fiber formation, migration, inflammation and oxidative stress (Mazak et al, 2004;Callera et al, 2005aCallera et al, , 2005bMiyata et al, 2008;Cai et al, 2017). Of special interest, aldosterone mediated by MR activation increased the expression of Gal-3 in a dose-and time-dependent manner in VSMCs (Calvier et al, 2013).…”
Section: Vascular Smooth Muscle Cellsmentioning
confidence: 99%